Clinical Significance of Blastocystis Sp. among Children with Leukemia - Zainab Khalid khalil (مجله كليه طب الكندي, 2019)
Background: Blastocystis spp. distributes world widely and the genus Blastocystis include many subtypes that are isolated from human intestinal tract. It is considered the most common parasite detected in human being.